2016
DOI: 10.1002/1873-3468.12294
|View full text |Cite
|
Sign up to set email alerts
|

From tRNA to miRNA: RNA‐folding contributes to correct entry into noncoding RNA pathways

Abstract: Edited by Wilhelm JustAlthough RNA are synthesized as single-stranded molecules, most of them are characterized by extensive secondary structures. Two RNA that require distinct folding for biogenesis and function are miRNA and tRNA. While miRNA are processed from hairpin-containing precursors, tRNA are folded into characteristic L-shaped structures. In addition, tRNA and their precursors are a rich source of RNA fragments. Recent findings suggest that their production might be determined by structural characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…These miRNAs are processed by Drosha independent, Dicer dependent mechanism. Then they enter the canonical miRNA biogenesis and they are transported to the cytoplasm by exportin 5 (29)(30)(31)(32). Some of the non-canonical pre-miRNA derived from tRNA and snoRNA (Figure 1, A2 panel).…”
Section: Mirna Biogenesismentioning
confidence: 99%
“…These miRNAs are processed by Drosha independent, Dicer dependent mechanism. Then they enter the canonical miRNA biogenesis and they are transported to the cytoplasm by exportin 5 (29)(30)(31)(32). Some of the non-canonical pre-miRNA derived from tRNA and snoRNA (Figure 1, A2 panel).…”
Section: Mirna Biogenesismentioning
confidence: 99%
“…miRNAs are found that circumvent both Dicer and Drosha, though most non‐canonical miRNAs are Drosha independent. miRNAs have been found in abundant non‐coding RNAs such as tRNAs, rRNAs, and snoRNAs 57–59 . These miRNAs are processed by enzymes involved in maturation of non‐coding RNA and not Drosha.…”
Section: Design Of Rnai Technologymentioning
confidence: 99%
“…The folding state and folding kinetics affect many processes in the life cycle of a tRNA molecule. In the tRNA maturation and degradation processes in eukaryotic cells, proteins or complexes such as Lupus autoantigen, RNase P, exportin-t, tRNA nucleotidyltransferase and xrn-1 interact with pre-tRNA or tRNA substrates by virtue of their structural characteristics (1)(2)(3)(4)(5). Moreover, tRNAs may change their folding state during some essential biological processes.…”
Section: Introductionmentioning
confidence: 99%